6(y+4)-2=52

Simple and best practice solution for 6(y+4)-2=52 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(y+4)-2=52 equation:


Simplifying
6(y + 4) + -2 = 52

Reorder the terms:
6(4 + y) + -2 = 52
(4 * 6 + y * 6) + -2 = 52
(24 + 6y) + -2 = 52

Reorder the terms:
24 + -2 + 6y = 52

Combine like terms: 24 + -2 = 22
22 + 6y = 52

Solving
22 + 6y = 52

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-22' to each side of the equation.
22 + -22 + 6y = 52 + -22

Combine like terms: 22 + -22 = 0
0 + 6y = 52 + -22
6y = 52 + -22

Combine like terms: 52 + -22 = 30
6y = 30

Divide each side by '6'.
y = 5

Simplifying
y = 5

See similar equations:

| 16-2n-5+8n=85 | | x/5=3/2 | | x=3+3.32i | | 16=-1d+6 | | 2b=-34 | | 10+3(x-13)=5(1-x)+14 | | -6x+2=-9+5x | | 4m+=13-m | | 7n-6+n=2(4n+3) | | (6a+11)=2a+83 | | x^2+121=2x^2 | | 7d-3d+5d-5-6d=0 | | b-2+3b+64=4 | | -136=8(1+6b) | | 16=2(x-1)-4 | | 4(3x+5)=104 | | 7.50=0.8c+0.5c | | 11=-7p+13+8p | | 6x-50=10-x | | 2m+23=7m-2 | | 0.5c-7.50= | | x^2-3x+24=0 | | 17x^2-22x+6=0 | | -4x+-40-6=-3-6 | | 4+4b=4 | | 7n-18+1=19 | | 8.2(s+4)=6.7x+5.2 | | b-2+3b+6=4 | | 6p-1=p+20 | | 6(x+8)=7X+3 | | 27*x=1800 | | 6(X+8)=7x-3 |

Equations solver categories